Predicting Anthropometric Dimensions Aimed at Ergonomic Design of Mounted Desktop Chairs for Thai University Students - Puttapanom, Sutanit (Naresuan University Engineering Journal, 2024)
While mounted desktop chairs have gained popularity in Thai universities for their space-saving features and affordability, many users experience discomfort and fatigue due to inconvenient adjustments or limited mobility. Addressing these concerns through improved ergonomic design can enhance user experience and make these chairs even more valuable additions to educational environments. However, achieving ergonomic design in these chairs can present challenges as acquiring accurate anthropometric measurements proves to be difficult, time-consuming, and costly. Therefore, this study applies forward stepwise regression analysis to estimate anthropometric dimensions needed for the chair design. The sample involved 857 students (430 females and 427 males) with ages ranging from 18 to 25 years old. Nineteen anthropometric measurements were collected. The data analysis results suggest two sets of linear regression models for predicting all anthropometric measurements needed by two sets of easy to measure inputs: Stature, Body Mass Index and Forearm-fingertip length, Waist circumference. All R2-values are greater than 70%. The predicted results obtained by proposed models were confirmed by actual anthropometry data which yielded P-values of paired sample t-tests for all outputs greater than 0.05. Moreover, new criteria determinants for some chairs’ dimensions and a recommended size are proposed.